Pembinaan Olah Raga Panahan sebagai Media Pendidikan Akhlâq pada Siswa Bandung Archery Club and School - Fitri Fitriyani; Ayi Sobarna; Nadri Taja (Bandung Conference Series: Islamic Education, 2023)
Abstract. Moral education is an effort to instill the values of goodness and truth in the human soul, so that they can distinguish between what is right and what is wrong. The process of moral education is not only studied in formal education but can be applied in non-formal education. One of them can be implemented through coaching archery sports. In Bandung there is an archery sports club called BACS (Bandung Archery Club and School). BACS is an archery club and school that accepts training to archery athletes through achievement. This study aims to: (1) what is the planning of moral education through archery coaching for Bandung Archery Club and School students?, (2) how is the implementation of moral education through archery sports coaching for Bandung Archery Club and School students?, and 3) how to evaluate moral education through archery coaching for Bandung Archery Club and School students? The research method used is descriptive method. While the nature of the research used is a qualitative approach. Data collection techniques using, observation, interviews, and documentation. The stages of data analysis include three activity flows: data reduction, data presentation and conclusion/verification. The research instruments in this study were the head of BACS, BACS trainers, students and parents of students. The results of the research obtained indicate that the implementation of moral education through the development of archery sports in its implementation has several stages including: in terms of planning, implementation and evaluation. Factors supporting and inhibiting the implementation of moral education through archery sports coaching at BACS include, supporting factors include: a) a conducive place, b) a structured program of activities, c) supporting infrastructure facilities, d) certified trainers. Inhibiting factors include: the background conditions of the students are different, making the approach to children carried out with different variations. With the existence of moral education which is implemented through archery, it is hoped that it can train habits so that it can form good morals and personality. Abstrak. Pendidikan akhlâq adalah upaya untuk menanamkan nili-nilai kebaikan dan kebenaran dalam jiwa manusia, sehingga dapat membedakan mana yang benar dan mana yang salah. Proses pendidikan akhlâq tidak hanya di pelajari di pendidikan formal saja melainkan dapat diterapkan di pendididkan non formal. Salah satunya dapat diimplementasikan melalui pembinaan olah raga panahan. Di Bandung terdapat salah satu club olah raga panahan yang bernama BACS (Bandung Archery Club and School). BACS merupakan club dan sekolah panahan yang menerima pembinaan ke atletan olah raga memanah jalur prestasi. Penelitian ini bertujuan untuk: (1) bagaimana perencanaan pendidikan akhlâq melalui pembinaan olah raga panahan pada siswa Bandung Archery Club and School?, (2) bagaimana pelaksanaan pendidikan akhlâq melalui pembinaan olah raga panahan pada siswa Bandung Archery Club and School?, dan 3) bagaimana evaluasi pendidikan akhlâq melalui pembinaan olah raga panahan pada siswa Bandung Archery Club and School?. Metode penelitian yang digunakan yaitu metode deskriptif. Sedangkan sifat penelitian yang digunakan yaitu dengan pendekatan kualitatif. Teknik pengumpulan data menggunakan, observasi, wawancara, dan dokumentasi. Adapun tahapan analisis data meliputi tiga alur kegiatan: reduksi data, penyajian data dan penarikan kesimpulan/ verifikasi. Instrument penelitian dalam penelitian ini adalah ketua BACS, pelatih BACS, siswa, dan orang tua siswa. Hasil penelitian yang di peroleh menunjukkan bahwa implementasi pendidikan akhlâq melalui pembinaan olah raga panahan dalam pelaksanaannya terdapat beberapa tahapan antara lain: dari segi perencanaan, pelaksanaan, dan evaluasi. Faktor pendukung dan penghambat implementasi pendidikan akhlâq melalui pembinaan olah raga panahan di BACS di antaranya, faktor pendukung meliputi: a) tempat yang kondusif, b) program kegiatan yang sudah terstruktur, c) fasilitas sarana prasarana yang mendukung, d) pelatih yang telah tersertifikasi. Faktor penghambat antara lain: kondisi background siswa yang berbeda-beda, menjadikan pendekatan pada anak dilakukan dengan variasi yang berbeda. Dengan adanya pendidikan akhlâq yang diimplementasikan melalui olah raga panahan, diharapkan dapat melatih habits (kebiasaan) sehingga dapat membentuk akhlâq dan kepribadian yang baik.